(untitled) (JURDIKSCA: Jurnal Pendidikan Agama Hindu Mahasiswa Pascasarjana, 2025)
Abstract This research aims to analyze the role of the Rāmāyaṇa epic as a spiritual education medium in Hindu religious learning, particularly in the modern era where spiritual values are often overshadowed by materialism and technological advancements. Using a qualitative descriptive approach, the study collected data through literature review, observation, and in-depth interviews with Hindu religious teachers, students, and cultural practitioners. The findings reveal that Rāmāyaṇa, with its profound spiritual and moral values such as dharma, karma, and moksha, serves as an effective medium for teaching ethical and spiritual principles. The study emphasizes the importance of integrating Rāmāyaṇa into the Hindu religious education curriculum and utilizing innovative methods, such as digital media, interactive storytelling, and cultural performances, to make it more accessible and engaging for younger generations. The research concludes that Rāmāyaṇa not only preserves cultural and spiritual heritage but also provides practical guidance for addressing contemporary moral and ethical challenges. Keywords: Rāmāyaṇa, spiritual education, Hindu religious learning, moral values.